Maternal complications associated with overweight and obesity in patients treated in a Peruvian public hospital, 2021 - Victorio-Huamán, Liseth Verónica (2024)
Objective: To determine maternal complications associated with overweight and obesity in patients treated in a Peruvian public hospital, from January to July 2021. Material and methods: Quantitative, descriptive, cross-sectional, correlational-causal transactional approach, in which the medical records of pregnant women diagnosed with overweight or obesity were analyzed, where the population was 1272 and the sample 295 pregnant women selected by simple random sampling. Results: The most frequent complications included cesarean delivery (41.0%), preeclampsia (20.7%), gestational diabetes (15.2%) and postpartum hemorrhage (14.3%). Furthermore, a statistically significant relationship will be observed between overweight and the presence of maternal complications (p=0.01). Conclusion: Pre-pregnancy overweight in pregnant women is associated with the presence of maternal complications, which underlines the need to implement preventive and comprehensive management strategies before and during pregnancy.